'Sound, listening and the queer art of history'. Issue 1 (2nd January 2018) - Evans, Jennifer V.
Abstract: This article explores the role of the museum audioguide as a relational, sensorially driven mode of making and communicating diverse histories. It argues that the artist Benny Nemerofsky Ramsay's use of voice, storytelling, gesture, movement, and sound helps create conditions for empathic listening, bridging the past and present and widening the spectrum of possibilities for new and diverse knowledge formations. This use of aesthetic and historical registers, the blending of fact with fiction, stresses multivalence and possibility over a singular narrative truth. The act of listening promotes a shared though subjective experience, one that challenges the exclusionary function of traditional museum displays, which turn on objective, documentary claims, while actually reflecting a hegemonic vision of the past. In this way, Nemerofsky offers a queer historical practice for how we might (re)present the diversity of past pasts.